2005
DOI: 10.1038/sj.pcan.4500833
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent androgen replacement for intense hypogonadism symptoms in castrated patients

Abstract: Objectives: For locally advanced prostate cancer management, medical androgen deprivation and surgical castration are alternatives. These hormonal treatments may cause a myriad of side effects, such as osteoporosis with increased risk of fractures, anemia, behavioral changes and lack of sexual interest. We evaluated the feasibility of intermittent androgen replacement in surgically castrated patients with significant side effects. Methods: Five patients with advanced prostate cancer, ranging from 71 to 77 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…[65][66][67][68] There was no evidence of prostate cancer recurrence in these men over periods of 0.5-12 years. The prospective case series included five men who had subcapsular orchiectomy to treat advanced prostatic carcinoma; these men had PSA increases while undergoing testosterone therapy for up to 2.5 years.…”
Section: 29mentioning
confidence: 70%
See 3 more Smart Citations
“…[65][66][67][68] There was no evidence of prostate cancer recurrence in these men over periods of 0.5-12 years. The prospective case series included five men who had subcapsular orchiectomy to treat advanced prostatic carcinoma; these men had PSA increases while undergoing testosterone therapy for up to 2.5 years.…”
Section: 29mentioning
confidence: 70%
“…[65][66][67][68] Further, men with high-grade PIN treated with testosterone did not have a greater increase in PSA or a significantly elevated risk of prostate cancer than testosterone-treated men without PIN. 54 Testosterone therapy did not cause a sudden progression to prostate cancer in men with PIN.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Several studies have shown that ART of hypogonadal patients with localized prostate cancer treated with radical prostatectomy or ADT has no adverse effect on prostate cancer progression (Kaufman and Graydon, 2004;Agarwal and Oefelein, 2005;Ferreira et al, 2006;Khera et al, 2009). Fowler and Whimore, (1981) observed that out of 52 metastatic prostate cancer patients who received ART, 45 exhibited increased cancer progression that could be reversed by androgen withdrawal, whereas 7 experienced symptomatic benefits.…”
Section: Art In Prostate Cancer Patientsmentioning
confidence: 99%